Pengaruh Etos Kerja Terhadap Kinerja pada Dinas Pemuda dan Olahraga (Dispora) Kota Bekasi - Kiki Setyawati; Catarina Cori (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
Human Resources (HR) or employees in a company or agency is a very important element to have. Good human resources are employees who are good in their work behavior in accordance with company or agency regulations. Employees who are able to carry out their duties and responsibilities in accordance with their behavior in completing their work. Companies or agencies must be able to pay attention to the performance patterns of their employees to achieve a synergistic relationship. The existence of Restrictions on Community Activities (PPKM) during the pandemic also affected the performance of the Bekasi City Youth and Sports Service (Dispora), which required that every day only around 25% to 50% of employees attend the Bekasi City Dispora office. This study focuses more on the ethos and performance of the Bekasi City Dispora by using a causality and correlative approach with the research variables namely the independent variable (work ethic) and the dependent variable (employee performance). Determining the number of samples in this study used an error level of 5%, so the sample used according to the table was 78 people. The results showed that the work ethic has a positive and very strong influence on the performance of employees at the Bekasi City Dispora. So the implication of this research is that employees need to have a high work ethic so that the resulting performance is also high and Dispora needs to build and improve the work ethic of employees in order to create the performance expected by the agency.